Evaluation of agreement between clinical and histopathological diagnosis of subtype of leprosy by skin punch biopsy - Poudel, Suman; Ranabhat, Sunita; Pun, Gita (Journal of Gandaki Medical College-Nepal, 2020)
Introduction: Leprosy is chronic granulomatous disease caused by Mycobacterium leprae. Clinically diagnosed cases of leprosy can be evaluated by punch biopsy. It can be classified according to Ridley and Jopling Classification.Objective: To study the different spectrum of leprosy and its Bacillary Index (BI), evaluate the agreement between clinical and histopathological diagnosis.Materials and Methods: This is a hospital based cross sectional retrospective study done for the period of 6 months from January to June 2019. The data were subjected to kappa analysis by using SPSS version 24 to see the agreement between clinical and histopathological diagnosis.Results: Out of 62 cases of clinically diagnosed cases of leprosy three (4.83%) cases turned out to be other granulomatous diseases. According to Ridley and Jopling classification, clinical and histopathological agreement was seen in 38 (61.29%) cases. Agreement of 100% was seen in Indeterminate leprosy (IL) and Borderline tuberculoid leprosy (BT). The BI was more in Lepromatous leprosy (LL), Borderline lepromatous (BL) whereas IL, BT and Tuberculoid leprosy (TT) showed less BI. Overall there was moderate agreement between clinical and histopathological diagnosis (kappa- 0.505) which was statistically significant (p value